Hydrogeochemical and Characteristics of Groundwater in Teluk Nilap Area, Rokan Hilir, Riau - Fitri Mairizki; Arief Yandra Putra; Widya Adiza Putri; Ferdyansyah (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Groundwater plays important role as the main water resource for human needs. The vulnerability of groundwater to contaminants both naturally and by human activities can be not avoided as a trigger for groundwater quality degradation. Hydrogeochemical become important highlights in groundwater studies because groundwater conditions in quality and quantity influenced by the geological formation of rock minerals in aquifer. Naturally, the condition of the research area which consists of peat swamps can also affect the characteristics of groundwater. The aims of this research are to determine groundwater types and groundwater facies in study area with an analytical approach using stiff diagram and piper diagram. The method used was purposive sampling by collecting data from dug wells at the research site. 5 samples from dug wells were used as representatives in the groundwater facies analysis. The groundwater facies analysis was carried out by measuring the concentration of major ions such as Na, K, Ca, Mg, Cl, SO4, and HCO3. The highest groundwater level was in the northern part of study area (7,84 m) while the lowest groundwater level was in the southwest part of study area (2,05 m). The results showed three types of groundwater based on stiff diagram as sodium chloride (NaCl), sodium sulfate (NaSO4) and magnesium sulfate (MgSO4). The lithology conditions that composed the aquifer affected the facies or origin of groundwater. The alluvium layer in the research area which rich in sodium (Na+) minerals with chloride (Cl-) or sulfate (SO42-) anions forms chloride sulfate facies (Cl+SO4) which were located in the middle to the south of the study area and sodium (potassium) chloride (sulfate) facies (Na(K)Cl(SO4)) which were distributed in the northern part of study area.